Capas de uma ditadura: o uso da sexualidade como recurso simbólico de resistência - NUNES, Márcia Silva (2024)
The present work brings a reflective research on the disc covers elaborated during the military dictatorship and that were censured, which will be analyzed through the Visual Design Grammar. The covers selected here to be analyzed are Gal Costa's album "As Indias" by Tom Zé "Todos os olhos" and by Caetano Veloso "Jóia". All will be analyzed through Visual Design Grammar, as well as, from the perspective of the rules imposed by the military dictatorship, which justifies the censorship given the above mentioned layers. The research used for the preparation of this work was the bibliographical research, which gave all support to make a historical survey of the period and the laws created in the dictatorship, laws that took many of the rights of the Brazilian population and imposed an ideal model "Of marriage, relationship, sexual choice and other society. But the bibliographical research also guided when to the concept, and analysis of said covers through the Grammar of Visual Design.